Pembelajaran Kapilaritas terhadap Pertumbuhan Tanaman untuk Melatih Kreativitas Anak Usia Dini - Adhiesta Kurnia Fikri Rosandi (Universitas Al-Hikmah Indonesia, 2019)
This research aims to describe the creativity of early childhood through learning capillarity towards plant growth in group B TK PKK Tunas Bangsa, Soko, Tuban. This Research using quantitative descriptive research methods with the type of experimental research. The design of this study is Pre-Experimental Designs using One-Group Pre-Test-Post-Test Designs. Based on the results of the analysis of the research data it can be concluded that the results of the pretest and posttest are normalized gain tests to determine an increase in children's creativity before and after learning. The result, an increase in children's creativity in capillary learning on plant growth with n-gain of 0.4 with moderate criteria.